Pemanfaatan e-commerce sebagai bekal wirausaha pada siswa SMA Unggulan Hafsha Zainul Hasan - Wahyu Nofiyan Hadi; Amrinatul Husna; Fiqih Fendi (P3HKI - Universitas Muhammadiyah Parepare, 2024)
This community engagement initiative aims to equip students at SMA Unggulan Hafsha Zainul Hasan with insights and practical understanding of digital marketing and e-commerce. The training curriculum encompasses establishing online storefronts, and implementing a dropshipping business model for online business management. Upon completion, participants are expected to generate income with minimal capital expenditure by leveraging their mobile devices, thereby potentially contributing to local economic empowerment. The methodology employed comprises three key phases: preparation, implementation, and interactive discussion with a question-and-answer session. The preparation phase involves the community service team's formulation of an execution plan and the procurement of necessary training resources. The implementation phase delivers foundational knowledge in digital marketing principles and the practical application of e-commerce platforms. Participants receive hands-on training in creating visually engaging marketing materials using Canva and in developing product marketing strategies. Furthermore, they receive direct guidance in setting up online stores and understanding the operational mechanics of a dropshipping business. The discussion and Q&A session provides a platform for participants to seek clarification on the presented material. The community service team also conducts formative assessments through questioning to evaluate participant comprehension. Post-activity evaluation indicates that 35 participants demonstrated a keen interest in pursuing online entrepreneurship through the dropshipping model, recognizing its potential for profitability, while 5 participants expressed less interest.